Pendidikan Multikultural Dipesantren - sunarto, sunarto (Universitas Islam Negeri Raden Intan Lampung, 2016)
Indonesia is a country made up of islands separated and bounded by the sea, so that Indonesia is a country that has a cultural diversity. The motto 'unity in diversity is a symbol which indicates that Indonesia is a unit that consists of diverse ethnicity, religion, language and culture that accompanies it. Indonesia's diverse cultures of the value of pluralism and multicultural, this must be addressed as a personality trait and pluralistic nation and a nation's wealth. Cultural differences should not be treated as a barrier and trigger conflict.Indonesian society should contribute to achieve this goal is no exception younger generation, mostly students. To build that education is an excellent medium to educate the nation's children are students as a potential successor to the nation to understand the cultural diversity of Indonesia and accept cultural differences such as the legacy of a country that always maintained its existence.Education is taught must be in accordance with the approach defined multiculturalism as an expression of awareness of cultural diversity, human rights, and the reduction or elimination of various types of prejudices to build a fair society and a life ahead. The education system in Indonesia is regulated and defined in an Act in the form of a national education system that is defined in the Act No. 20 of 2003.